2022
DOI: 10.1186/s40543-022-00345-2
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of Plk1 PBD inhibitor KBJK557 as a tumor growth suppressor in non-small cell lung cancer

Abstract: Lung cancer is the second most commonly reported type of cancer worldwide. Approximately 80–85% of lung cancer occurrences are accounted by non-small cell lung cancer (NSCLC). Polo-like kinase-1 (Plk1) plays multiple roles in cell cycle progression and its overexpression is observed in majority of malignancies, including NSCLC. A combination of frontline drugs and inhibitors targeting the Plk kinase domain (KD) has been used to overcome drug resistance in NSCLC. Plk1 KD inhibitors are highly prone to cross-rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…In accordance with our findings, several earlier studies have also reported the cell cycle arrest of cancer cells at the DNA damage G2/M checkpoint and apoptosis after PLK1 inhibition [58][59][60]. In fact, strong PLK1 associations with the A549 cells [61][62][63] further strengthen the outcomes. However, it is too early to provide the conclusive remark on the applicability of C8 as a dual therapeutic agent for tuberculosis and lung cancer.…”
Section: Dapi Assaysupporting
confidence: 92%
“…In accordance with our findings, several earlier studies have also reported the cell cycle arrest of cancer cells at the DNA damage G2/M checkpoint and apoptosis after PLK1 inhibition [58][59][60]. In fact, strong PLK1 associations with the A549 cells [61][62][63] further strengthen the outcomes. However, it is too early to provide the conclusive remark on the applicability of C8 as a dual therapeutic agent for tuberculosis and lung cancer.…”
Section: Dapi Assaysupporting
confidence: 92%
“…For instance, evaluation of PLK1 expression level in NSCLC cell lines, including A549, PC9, and H1975 showed a significant PLK1 level similar to that of HeLa cells in Western blots (Figure S6). , Based on the aforementioned facts and inspired by the prominent potency of DD-2 against HeLa cells, we intended to investigate the degradation of the PLK1 in those NSCLC cell lines, as shown in Figure e–g.…”
Section: Resultsmentioning
confidence: 99%
“…In the past few decades, considerable efforts have been devoted to the discovery of several kinase domain targeting inhibitors, including GSK461364, BI2536, volasertib, ON 01910, NMS-P937, and TAK-960 , and promoted to clinical trials. However, most of the inhibitors fail to cross clinical phase trail-II due to the cross-reactivity that arises from a high degree of homogenicity of ATP binding pockets in various kinases. , Alternatively, targeting the unique allosteric site (PBD) of PLK1 was found to be a valid strategy to overcome the cross-reactivity and subsequent side effects. , Many research groups, including our group, have made significant breakthroughs in the discovery of peptide and small molecule-based PLK1 PBD inhibitors. , …”
Section: Introductionmentioning
confidence: 99%